Marketing Strategy For Educational Services Based On Digital Personalization In The Post-Pandemic Era : Phenomenological Study On Online Course Institutions - Riu, Isma Azis (Abadi Institute, 2025)
The post-pandemic era has intensified the need for personalized digital education, particularly in non-formal sectors where adaptive strategies are critical to addressing diverse learner needs. This phenomenological study explores how online course institutions in Makassar, Indonesia, utilize artificial intelligence (AI) and data analytics to personalize educational services, emphasizing socio-cultural and ethical dimensions. Through semi-structured interviews, observations, and document analysis involving 15 participants (educators, administrators, and learners), the study reveals that while AI-driven tools enhance engagement through adaptive content and predictive analytics, their implementation faces challenges such as infrastructural limitations, generational resistance, and ethical concerns over data privacy and algorithmic bias. Culturally resonant adaptations such as localized interfaces and virtual pattudang (community gatherings) emerged as key strategies to bridge technological and communal values. However, participants underscored the necessity of hybrid models that balance automation with human mentorship, alongside decentralized policies to support equitable innovation. The findings advocate for community-driven approaches in Indonesia’s National Digital Literacy Framework, prioritizing ethics-by-design and partnerships between institutions, tech startups, and policymakers. This research contributes to global discourse on AI in education by highlighting the interplay between technological agility and cultural humility, offering actionable insights for community service (PKM) initiatives aimed at fostering inclusive, context-sensitive education in urban Indonesia.